Research on the Influence of Eccentricity on the Leakage Characteristics of Piston Rings - Chunrui Liu; Gang Chen; Gaohui Xiao; Xingyun Jia; Lidong He (IEEE Access)
Piston rings are more susceptible to eccentricity in a complex service environment, which affects the overall performance and reliability of wet clutches. Therefore, in this study, the influence of eccentricity on the leakage characteristics of piston rings was investigated using numerical simulations. An eccentric experiment bench of piston rings was also built in this research, and an eccentric leakage experiment of piston rings was performed using an experimental bench. The experimental results show that when the radial eccentricity is 0.3 mm, compared with the piston rings without radial eccentricity, the leakage increases by approximately 85.0% at the maximum. When the angular eccentricity is 0.1 degrees, compared with piston rings without angular eccentricity, the leakage increases by approximately 23.5% at the maximum. The research results reveal the effect of radial and angular eccentricities on the leakage of piston rings, which can provide support for improving the overall performance and reliability of wet clutches.